The impact of China’s fertility policies on the future electricity demand of residential households - Li Wang; Li Wang; Xin-Hua Zhang (Frontiers in Energy Research, 2023)
Under China’s “comprehensive two-child” policy (UTCP) and “three-child” policy (TCP), household’s age structure is bound to change, and this change will further have an impact on household demand for electricity. In order to accurately forecast the impact of fertility policy on residential household electricity demand, we firstly construct a prediction model with annual household electricity consumption as the dependent variable and average electricity price and household-level old-age dependency ratio (HODR) as the independent variables. Second, we use the cohort-component projection model (CCPM) to construct a population prediction model to obtain the macrolevel old-age dependency ratio (MODR). Third, based on the interactive ritual chain (IRC) theory, we explore the statistical relationship between macrolevel old-age dependency ratio and household-level old-age dependency ratio to obtain a prediction method for the household-level old-age dependency ratio. Finally, we take five households as examples and predict their electricity demand from 2022–2035. The following conclusions are obtained: 1) the average electricity price and the household-level old-age dependency ratio have a significant suppressive effect on the electricity demand; 2) for households without the pressure of old-age dependency, the Under China’s “comprehensive two-child” policy’s contribution to electricity demand is pregnant, while “three-child” policy’s is limited; 3) the Under China’s “comprehensive two-child” policy and “three-child” policy cannot fundamentally curb the declining trend of residential electricity demand of China in the long term.